2017
DOI: 10.18805/ijar.b-3445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foot and mouth disease vaccination on seminal traits in pure Holstein Friesian bulls

Abstract: The present investigation was carried out to study the effect of foot and mouth disease vaccination on seminal traits of 30 Holstein Friesian (HF) bulls, 3-5 years old, maintained at BAIF Central Research Station, Uruli Kanchan, Pune, India. The study period was from August to September 2013 and semen quality traits were evaluated on each bull maintained under identical feeding and management regimes. A total of 180 semen ejaculates were collected with one ejaculate from each bull at 3 days interval in a week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the present study indicated no significant difference results for individual motility on postvaccination (M = 80.90, SD = 8.06) over prevaccination (M = 78.51, SD = 10.86), t(74) = -1.72, p = 0.95 and not a significant difference for sperm concentration on post-vaccination (M = 1435.00, SD = 437.11) over pre-vaccination (M = 1266.75, SD = 422.60), t(74) = -4.35, p = 1.00 in Bali cattle bull. These results were in line with those reported by Gupta et al (2017). The analysis results from the parameters of individual motility (%), abnormalities (%), concentration, and volume of 25 Bali cattle semen-donor bulls before and after FMD vaccination are present in Table 1.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study indicated no significant difference results for individual motility on postvaccination (M = 80.90, SD = 8.06) over prevaccination (M = 78.51, SD = 10.86), t(74) = -1.72, p = 0.95 and not a significant difference for sperm concentration on post-vaccination (M = 1435.00, SD = 437.11) over pre-vaccination (M = 1266.75, SD = 422.60), t(74) = -4.35, p = 1.00 in Bali cattle bull. These results were in line with those reported by Gupta et al (2017). The analysis results from the parameters of individual motility (%), abnormalities (%), concentration, and volume of 25 Bali cattle semen-donor bulls before and after FMD vaccination are present in Table 1.…”
Section: Resultssupporting
confidence: 90%
“…These results are contrary to those previously reported by Perumal et al (2013) in Mithun bull semen following FMD vaccination. Furthermore, Sirohi et al (2016) and Gupta et al (2017) also reported an increase in abnormalities in the head, midpiece, and tail of Frieswal and Friesian Holstein bull's spermatozoa due to FMD vaccination.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Gosálvez et al (61) also recorded a significant increase in sperm DNA damage after vaccination of rams, but observed that the negative impact was reversible. In another study, Gupta et al (62) reported a deleterious effect of foot-and-mouth disease vaccine on plasma membrane integrity and morphology of bull sperm.…”
Section: Vaccination Stressmentioning
confidence: 97%
“…However, more emphasis is still required to be laid on vaccination of exotic and crossbred bulls, as they are more prone to Foot and Mouth diseases (FMD), Hemorrhagic Septicemia (HS), Black Quarter (BQ) and other diseases (Bhakat et al 2011a). Available report on the effect of vaccination on semen quality are conflicting in nature; while some studies reported no significant effect of vaccination on semen quality (Mangurkar et al 2000), others found increased incidence of sperm abnormalities (Pankaj et al 2007). Semen quality affected by vaccination (Bhakat et al 2008(Bhakat et al , 2010(Bhakat et al , 2011a(Bhakat et al , 2015 as a consequence of stress caused by a rise in the body as well as testicular temperature during the post-vaccination period.…”
mentioning
confidence: 99%